2019
DOI: 10.30802/aalas-jaalas-19-000008
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex Immunochromatographic Assay for Serologic Diagnosis of Major Infectious Diseases in Laboratory Mice

Abstract: Serologic monitoring of infectious diseases is important for microbial control in colonies of laboratory mice. Rapid and simple tests that do not require killing animals are valuable for this purpose. In this study, we developed a multiplex immunochromatographic assay (ICA) for detection of antibodies to mouse hepatitis virus (MHV), Sendai virus (also known as hemagglutinating virus of Japan [HVJ]), and Clostridium piliforme (The pathogen that causes Tyzzer disease), which are major infectious diseases in mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Niepceron and Licois ( 2010 ) established a nested PCR method with high sensitivity for the detection of C. piliforme ; Tosa et al. ( 2019 ) established a multiplex immunochromatographic method for rapid and simple detection of multiple pathogens, including C. piliforme . Rapid, instant and accurate nucleic acid detection is necessary in certain industries; however, some centres are not equipped with complex instruments, such as a PCR system (Wang et al., 2023 ; Yan et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Niepceron and Licois ( 2010 ) established a nested PCR method with high sensitivity for the detection of C. piliforme ; Tosa et al. ( 2019 ) established a multiplex immunochromatographic method for rapid and simple detection of multiple pathogens, including C. piliforme . Rapid, instant and accurate nucleic acid detection is necessary in certain industries; however, some centres are not equipped with complex instruments, such as a PCR system (Wang et al., 2023 ; Yan et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…A multiplex microbead immunoassay and PCR-based detection of antigen in feces have been reported as methods for diagnosing infectious disease without euthanizing animals [1][2][3][4][5][6]. We previously reported that the use of a multiplex immunochromatographic assay (ICA) enabled simultaneous and specific detection of antibodies to mouse hepatitis virus (MHV), Sendai virus (also known hemagglutinating virus of Japan, HVJ), and Clostridium piliforme (the pathogen that causes Tyzzer disease) with small amounts of blood that can be collected without euthanizing mice [7]. Additionally, multiplex ICA is useful for in-house monitoring due to its ability to simply and rapidly detect antibodies against multiple antigens without the need for an expensive, dedicated analyzer.…”
Section: Introductionmentioning
confidence: 99%